Potential Output and Output Gap in Nepal - Bhandari, Pitambar (NRB Economic Review, 2010)
The potential output and output gap are key variables in identifying the scope for sustainable noninflationary growth and assessment of the stance of macroeconomic policies. This paper estimates potential output and the output gap in Nepal by different methodologies. The different methodologies produce similar results followed by analysis and observations. The results show that the output gaps were within relatively narrower band since 1990s. The results also reveal some sign of overheating in recent years. The results from production function approach indicate that total factor productivity is declining continuously in the last decade limiting the scope for demand management policies to attain high and sustainable economic growth.